Use of dried distiller’s grains with soluble for swine diets - Hastad, C.W.; Groesbeck, C.N.; Lawrence, K.R.; Lenehan, N.A.; Keegan, T.P.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A large increase in the number of ethanol plants has lead to increased availability of dried distiller’s grains with solubles (DDGS). New plants also have improved processing techniques, which makes DDGS more attractive to use in swine diets. Two experiments were conducted to determine the energy value of DDGS. In Experiment 1, 360 pigs (each initially 38.5 lb) were used in a 22 d growth assay. Treatments consisted of five corn-soybean meal-based diets with added wheat bran or soy oil to provide five different energy densities ranging from 1,390 to 1,604 Kcal/lb ME. The objective was to use responses to the wide range of energy densities to calculate an energy value for two sources of DDGS. Because it is speculated that newer ethanol plants produce a better quality DDGS than older plants, we selected one relatively new plant in Minnesota, and a second, older plant in Nebraska as separate sources of DDGS. Pigs were fed four additional diets, including either 15 or 30% DDGS from one of the two different sources. For the overall 22 d study, increasing energy increased ADG (linear; P<0.01), reduced ADFI (linear; P< 0.01), and improved F/G (linear; P<0.01). Because of the linear response to increasing energy in our five basal diets, the F/G of pigs fed the diets containing DDGS could be compared to the F/G of the control diets. Thus, we estimated the ME of 1,586 and 1,419 kcal ME/lb for the Minnesota and Nebraska DDGS sources, respectively. In Experiment 2, eight barrows (each initially 98.3 lb) were used in a Latin square design to determine the ME of the two DDGS sources used in Experiment 1. Diets were made up of 97% DDGS supplemented with crystalline amino acids, vitamins, and minerals to meet or exceed the pigs’ nutrient requirements. There were no differences (P>0.49) for any growth traits; however, estimated digestible energy (DE) (1,756 vs. 1,691; P<0.02) and ME values (1,677 vs. 1,627; P<0.05) were greater than calculated in the growth trial. The results of these two studies with the same batches of DDGS suggest possible variation in the energy value of DDGS based on how it is measured. In a nutrient balance study where pigs are individually fed a limited amount of feed, ME values were estimated to be higher than predicted from extrapolating our results from a growth trial. This leads us to speculate that in the growth trial, the decrease in ADFI and improvement in F/G observed from increasing DDGS may not have been a result of its increased energy content, but rather a palatability problem. Therefore, while it appears that the ME content of DDGS produced from relatively new processing plants appears to be comparable to that of corn, palatability problems may affect performance of pigs fed diets containing DDGS. Therefore, producers should exercise caution and evaluate potential variation and palatability before incorporating DDGS into their nutrition programs.
Keywords: Distiller's dried grains with solubles; Energy; Swine